2015
DOI: 10.1590/0037-8682-0168-2014
|View full text |Cite
|
Sign up to set email alerts
|

Congenital and maternal syphilis in the capital of Brazil

Abstract: Introduction: This study aimed to describe the epidemiology of congenital and maternal syphilis in the Brazilian Federal District in 2010. Methods: A retrospective descriptive study was conducted on the basis of the cases recorded in the System of Notifi able Disease Information. Results: The study population comprised 133 cases of congenital syphilis; of these, 116 (52.6%) mothers received prenatal care, and 70 (60.4%) were diagnosed with syphilis during pregnancy. Only 1 mother was adequately treated, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 7 publications
3
19
0
19
Order By: Relevance
“…Many CS cases would have been prevented if the MoH recommendations for SiP were fully adopted. Other Brazilian studies also showed that prenatal care did not ensure an early SiP diagnosis, nor the timely and adequate treatment of pregnant women and their sexual partners, and did not prevent miscarriages, stillbirths, and deaths related to CS [3][4][5][6][7][8][9][10] . In SP state, from 2007 to 2014, there were 1,012 fetal losses due to CS (126 deaths, and 886 miscarriages and stillbirths) 5 .…”
mentioning
confidence: 99%
“…Many CS cases would have been prevented if the MoH recommendations for SiP were fully adopted. Other Brazilian studies also showed that prenatal care did not ensure an early SiP diagnosis, nor the timely and adequate treatment of pregnant women and their sexual partners, and did not prevent miscarriages, stillbirths, and deaths related to CS [3][4][5][6][7][8][9][10] . In SP state, from 2007 to 2014, there were 1,012 fetal losses due to CS (126 deaths, and 886 miscarriages and stillbirths) 5 .…”
mentioning
confidence: 99%
“…The proportion of women who were inadequately treated and untreated totalled approximately 70% in this study, although this figure is still lower than that found in the Federal District, in which a study of 100 women with syphilis during pregnancy found that only 1% had adequate treatment of the disease. This difference was probably due to the large number of untreated partners (75.2%) identified in this study 14 . It is necessary to invest in the education of patients regarding the treatment of syphilis in pregnancy and to emphasise that treatment of the woman's partner is essential.…”
Section: Discussionmentioning
confidence: 69%
“…The analysis of the information showed that according to the clinical classification, most cases were attributed as primary syphilis, not being in accordance with the pathophysiology of the disease [4]. Furthermore, a recent study [23] identified that health professionals had insufficient technical skills to address the problem of syphilis in prenatal care, especially regarding syphilis treatment and control [9,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%